Re-description and iconography of Tabanus striatus (Diptera: Tabanidae) a common livestock pest and mechanical vector of Trypanosoma evansi in Asia - Wongthangsiri, Denphum; Desquesnesb, Marc; Jittapalapong, Sathaporn; Chareonviriyaphap, Theeraphap (Agriculture and Natural Resources, 2019)
Female tabanids are regarded as mechanical vectors of several pathogens and are an important livestock pest. Approximately 4,400 species of tabanids are distributed in all kinds of landscape. Control-limiting methods, including environmental and zootechnical management, require species identification of the flies in a given area. Studies carried out in Thailand have shown a limited species diversity in livestock farms; nevertheless, identification is always difficult when a non-specialist uses dichotomic keys. New user-friendly guidelines recently published, facilitate the description and identification of biting flies. Following these guidelines the most common species, Tabanus striatus, was re-described with emphasis on the key points allowing distinction from the morphologically close T. megalops. In addition, a rich original iconography was provided with 30 pictures of this common biting fly, whose distribution spreads from Pakistan and India to China, and from Lao to Thailand and Vietnam.